Survivability in Nilagiri and Nilagiri Synthetic Sheep: Genetic and Non-Genetic Effect - Chaudhari, B; Rajendran, R; Venkatamanan, R; Sivasalem, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Data on 9333 records of Sheep Breeding Research Station, Sandynallah, The Nilagiris (Tamil Nadu) available for 25 years (1989 to 2015) were analyzed for pre- and post-weaning survivability (0- 3 months, 3-6 months, 6-9 months and 9-12 months of age). The effect of various genetic and non-genetic factors, viz., breed, contemporary group of birth, birth type, inbreeding, sex and birth weight on survivability were analyzed. The least squares means for survivability during 0-3, 3-6, 6-9 and 9-12 months were 92.8 ± 0.8, 95.3 ± 0.8, 98.6 ± 0.6 and 98.2 ± 0.7 % for Nilagiri sheep and 89.9 ± 1.0, 92.9 ± 1.0, 96.9 ± 0.7 and 97.0 ± 0.8 % for Nilagiri synthetic sheep, respectively. Breed and contemporary group of birth had significant (P
Keywords: Nilagiri; Nilagiri Synthetic; Sheep; Lamb survivability